PENGARUH HARGA, LOKASI, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI AYAM KHAS NUSANTARA SUZUYA MARELAN PLAZA - Faris, Salman; Limbong, Ryandi; Hutagaol, Arnold; Panjaitan, Torang Daud; Nasib (Jurnal Ekonomi Bisnis Manajemen Prima, 2025)
This study aims to analyze the partial and simultaneous effects of price, location, and service quality variables on purchasing decisions at Ayam Khas Nusantara Suzuya Marelan Plaza. The research method used is quantitative with a survey approach. Data was collected through questionnaires distributed to 100 respondents who were customers of Ayam Khas Nusantara Suzuya Marelan Plaza. Data analysis was carried out using multiple linear regression to test the effect of independent variables (price, location, and service quality) on the dependent variable (purchase decision). The results showed that price, location, and service quality significantly influenced the decision to purchase Ayam Khas Nusantara at Suzuya Marelan. Among the three variables, service quality has the most dominant influence on purchasing decisions. The amount of influence found was 64.2%, the rest was influenced by variables not examined in this study. These findings provide managerial implications for Suzuya Marelan to continue to maintain and improve service quality, as well as consider price and location factors in marketing strategies to increase customer satisfaction and loyalty.